2022
DOI: 10.3346/jkms.2022.37.e235
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Gastrointestinal Cancer on Daily Intake of Low-Dose BaP in C57BL/6 for 60 Days

Abstract: Background Benzo(a)pyrene (BaP) is a carcinogenic compound in contaminated foodstuffs. The effect of oral intake of the environmental carcinogen BaP under low doses and frequent exposure on a digestive system has not been thoroughly verified. Methods In this regard, this study was conducted to prove the toxicity effects of BaP on the stomach and colon tissue after exposure to C57BL/6 mouse (3 and 6 µg/kg) following daily oral administration for 60 days. This study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Various in vivo and in vitro experiments in human cell lines and rodents had shown that B[a]P induces different downstream processes through the activation of AhR (Almendarez-Reyna et al, 2023; Jin et al, 2022; Lou et al, 2022; Tsai et al, 2015). Subsequently, B[a]P exposure has been observed to induce oxidative stress in cells through increased interleukin 6 (IL-6) production as a result of activated NF-κB signaling pathway (Jin et al, 2022; Malik et al, 2018; Zheng et al, 2022). The oxidative stress caused by B[a]P exposure has been studied as a cause for disruption of lysosomes, eventually leading to dysfunctional autophagy (Gorria et al, 2008; Li et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various in vivo and in vitro experiments in human cell lines and rodents had shown that B[a]P induces different downstream processes through the activation of AhR (Almendarez-Reyna et al, 2023; Jin et al, 2022; Lou et al, 2022; Tsai et al, 2015). Subsequently, B[a]P exposure has been observed to induce oxidative stress in cells through increased interleukin 6 (IL-6) production as a result of activated NF-κB signaling pathway (Jin et al, 2022; Malik et al, 2018; Zheng et al, 2022). The oxidative stress caused by B[a]P exposure has been studied as a cause for disruption of lysosomes, eventually leading to dysfunctional autophagy (Gorria et al, 2008; Li et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 29, 2024. ; https://doi.org /10.1101/2024.03.27.586984 doi: bioRxiv preprint Subsequently, B[a]P exposure has been observed to induce oxidative stress in cells through increased interleukin 6 (IL-6) production as a result of activated NF-κB signaling pathway (Jin et al, 2022;Malik et al, 2018;Zheng et al, 2022). The oxidative stress caused by B[a]P exposure has been studied as a cause for disruption of lysosomes, eventually leading to dysfunctional autophagy (Gorria et al, 2008;Li et al, 2023).…”
Section: Toxicity Pathway Linking B[a]p Exposure To Liver Fibrosis In...mentioning
confidence: 99%
“…In addition, the quantity and frequency of the food consumed might affect human exposure to HCAs ( 35 ). BaP was shown to induce stomach and liver cancer ( 36 ). In 2006, FAO/WHO claimed that BaP causes tumours of the gastrointestinal tract, liver, lungs, mammary glands and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that changes in intestinal microbiota are associated with human diseases, and the toxic effects of BaP have been widely characterized. 23 However, the effect of BaP on the intestinal tract is uncertain. This study observed that BaP exposure destroyed the gut micro ora of mice, leading to the abnormal in ammatory responses and pyroptotic damage, and changes in intestinal function.…”
Section: Discussionmentioning
confidence: 99%